2023
DOI: 10.1007/s00203-023-03467-2
|View full text |Cite
|
Sign up to set email alerts
|

A mini review on green nanotechnology and its development in biological effects

Abstract: The utilization of living organisms for the creation of inorganic nanoscale particles is a potential new development in the realm of biotechnology. An essential milestone in the realm of nanotechnology is the process of creating dependable and environmentally acceptable metallic nanoparticles. Due to its increasing popularity and ease, use of ambient biological resources is quickly becoming more significant in this field of study. The phrase “green nanotechnology” has gained a lot of attention and refers to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(30 citation statements)
references
References 125 publications
0
30
0
Order By: Relevance
“…Further research is needed to explore its applications and potential environmental impact. Furthermore, Shaheen ( 2021 ) and Salem ( 2023 ) reported that the biosynthesis of nanoparticles involves bio-reduction capping and trapping. Enzymes present in the cell wall of microorganisms convert metal ions and metal oxide into nanoparticles, which then diffuse away from the cell membrane.…”
Section: Resultsmentioning
confidence: 99%
“…Further research is needed to explore its applications and potential environmental impact. Furthermore, Shaheen ( 2021 ) and Salem ( 2023 ) reported that the biosynthesis of nanoparticles involves bio-reduction capping and trapping. Enzymes present in the cell wall of microorganisms convert metal ions and metal oxide into nanoparticles, which then diffuse away from the cell membrane.…”
Section: Resultsmentioning
confidence: 99%
“…Biosynthesis of metal sulfides by bacteria, fungi, algae and actinomycetes has garnered immense attention in the field of nanotechnology. 95 Bacteria possess the capability to reduce metallic ions into nanoparticles and are one of the most suitable candidates for metal sulfide nanoparticles because of their manageable nature and high growth rate. Metal complexation typically involves bacterial cell wall functional groups like hydroxyl, amine, and carbonyl groups.…”
Section: Synthetic Approaches For Metal Sulfide Nanoparticlesmentioning
confidence: 99%
“…In addition, natural products derived from plants, algae, bacteria, and fungi are effective as reducing, stabilizing, and capping agents during nanoparticle synthesis. 13 For example, filtrates of Arthrobotrys spp., Fusarium spp., Aspergillus spp., and Penicillium spp. containing multiple enzymes and metabolites can be used as biological reducing agents to produce either intracellular or extracellular metallic nanoparticles.…”
Section: Introductionmentioning
confidence: 99%